A bezier curve optimization method based on segmentation factor (t) for path planning in autonomous navigation - Vinayak, Akhil; Muhammad Aizzat, Zakaria; Baarath, K. (AIP Publishing, 2022)
Path planning plays a major role in autonomous navigation. Different curve fitting methods are used in creating path for autonomous vehicles. Among those Bezier curves are widely used to create path especially in roundabouts due to their special properties. The primary factor that affects the shape and curvature of the Bezier curve is the control points. Researchers have established equations for finding the control points of a Bezier curve passing through selected points. The two critical elements that determine the control points are the random points selected for control point calculation and the segmentation factor (